Quantum Private Comparison Protocol with Cluster States - Min Hou; Yue Wu (Axioms)
In this paper, we introduce a quantum private comparison (QPC) protocol designed for two players to securely and privately assess the equality of their private information. The protocol utilizes four-particle cluster states prepared by a semi-honest third party (TP), who strictly adheres to the protocol without deviation or collusion with any participant. The TP facilitates the private comparison by enabling users to encode their information through bit-flip or phase-shift operators applied to the received quantum sequences. Once the information is encoded, the sequences are returned to the TP, who can derive the comparison results without accessing any details of the private information. This design ensures correctness, privacy, and fairness throughout the process. The QPC protocol is robust against both external threats and participant attacks due to the incorporation of the decoy-state method and quantum key distribution techniques. Additionally, the protocol employs unitary operations and Bell-basis measurements, enhancing its technical feasibility for practical implementation. Notably, the proposed protocol achieves a qubit efficiency of up to 50%. This efficiency, combined with its strong security features, establishes the QPC protocol as a promising solution for private information comparisons within the realm of quantum cryptography.